Multimodal Sexual Signaling and Mating Behavior in Olive Baboons (Papio anubis). Issue 7 (16th April 2013) - RIGAILL, LUCIE; HIGHAM, JAMES P.; LEE, PHYLLIS C.; BLIN, AMANDINE; GARCIA, CÉCILE; Higham, James P.; Semple, Stuart
Abstract In primate species, mating decisions seem to be based on multiple signal elements with different roles in the signaling of female reproductive status. Whereas some primate signals are relatively well described (e.g., sexual swellings and copulation calls), studies that simultaneously assess visual, auditory, behavioral, and olfactory cues as signals of reproductive state are rarely undertaken. We used data on variation in sexual behaviors and sexual swellings in relation to the fertile period (estimated from the date of swelling detumescence) from a troop of semi‐free ranging olive baboons (Papio anubis) to assess how different signals influence patterns of mate choice. Using an objective and quantitative measure of swelling size and color, along with detailed data on sexual behaviors from 13 cycles of nine adult females, we found that fine‐scale variation in sexual swelling size, female behavior and copulation call rates could advertise the beginning of the fertile phase whereas swelling color did not. Rates of olfactory inspections by males also increased during the fertile phase, suggesting that olfactory signals were of interest to males and may contain information about ovulation. There was no relationship between female characteristics (age and rank) and the expression of sexual signals, except for proceptive behaviors which increased with female rank. Males displayed more sexual behaviors such as approaches and holding and tended to direct more ejaculatory mounts during the fertile phase. All together, we suggest that whereas all males could have information concerning the timing of ovulation through female proceptive behaviors and swelling size, consorting males may have access to additional signals (olfactory cues). Sexual communication in olive baboons is consistent with a multimodal framework for fertility signaling, potentially allowing males and females to establish different mating strategies. The possible selective pressures leading to multi‐modal signaling are discussed. Am. J. Primatol. 75:774–787, 2013. © 2013 Wiley Periodicals, Inc.